Wear and osteolysis around total knee arthroplasty - Naudie, Douglas D R; Ammeen, Deborah J; Engh, Gerard A; Rorabeck, Cecil H (Journal of the American Academy of Orthopaedic Surgeons, 2007)
Osteolysis induced by wear debris of ultra-high-molecular-weight polyethylene has emerged as a significant problem after total knee arthroplasty. The generation of polyethylene wear and the development of osteolysis around total knee arthroplasty are caused by a combination of patient, implant, and surgical factors. Activity level over time may be the most important patient factor affecting the loads placed on a total knee replacement, but it is the most difficult to manage. Multiple factors related to the manufacturing of the polyethylene implant influence the extent of wear, and surgeons should be cautious in considering enhanced polyethylenes pending results of further investigations. The optimal design of the articular bearing surface remains controversial but needs to be considered with respect to the stresses imparted on component-bone and modular tibial backside interfaces. Surgical factors, including restoration of alignment and ligament balance, are important for long-term durability of the implant. Methods of measuring the wear of total knee implants are still evolving. Thus, when confronted with a worn total knee implant and developing osteolysis, the surgeon should consider each of these factors in selecting the best management option to eliminate the source of debris and minimize the potential for wear and osteolysis following revision.